The emergence of non-state actors in enhancing Malaysia's relationship with the GCC countries - Mohd Afandi, Salleh; Fadzli, Adam; Mohd Fauzi, Abu-Hussin (Universiti Putra Malaysia, 2015)
For more than 40 years, there has been growing interest in the socio-political and economic interactions between Malaysia and individual Arab Gulf States. This is most likely because of the economic interaction between these nations and Malaysia as well as the religious affinity between Malaysia and the Arab Gulf states. This has invariably led to the proliferation and establishment of numerous non-state actors who are also playing momentous roles in enhancing bilateral relationships. The aim of this paper is not only to examine and investigate the influence and contributions of non-state actors in enhancing Malaysia’s relationship with the Arab Gulf states but also to provide a significant attempt to assess the role of Malaysian non-state actors in shaping future direction with the Arab Gulf countries and the extent to which Malaysian foreign policy has intensified the role of non-state actors.